Acceptance and Commitment Therapy Dalam Mengurangi Tingkat Kecemasan Pada Perempuan Yang Mengalami Kekerasan Verbal ( Pendekatan Studi Kasus ) - Pratidina, Putu Ayu Onik; Anggreni, Ni Wayan Yuli; Wistarini, Ni Nyoman Imas Pradnyanita; Dewi, Ni Nyoman Diah Adnyani (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2025)
This study aimed to examine the effectiveness of Acceptance and Commitment Therapy (ACT) in reducing anxiety in an emerging adult woman who experienced verbal abuse since childhood. The research used a case study design with one participant selected through purposive sampling. The subject was a 20-year-old woman categorized as an emerging adult, experiencing high levels of anxiety due to prolonged verbal abuse during childhood. A mixed-methods approach was applied, combining qualitative data from interviews and observations, and quantitative data using the GAD-7 anxiety scale. The ACT intervention used an A-B design, consisting of one baseline phase and one treatment phase, with a total of four treatment sessions. Quantitative analysis compared GAD-7 scores before and after ACT, showing a reduction in anxiety from the severe to the mild category. Qualitative findings further supported this result, revealing behavioral changes in the subject. Initially fearful of new social situations and hesitant to take new opportunities, the subject began to engage more confidently with new people and activities. The subject also showed improvements in classroom participation and online self-expression. These findings indicate that ACT can effectively enhance psychological flexibility and reduce anxiety, especially in early adult women with a history of verbal abuse.